PEMAHAMAN ASPEK-ASPEK HUKUM GADAI DALAM MEWUJUDKAN PERLINDUNGAN HUKUM TERHADAP KONSUMEN - Agus Suwandono (Jurnal Pelayanan Hubungan Masyarakat, 2023)
The purpose of this legal counseling is to increase public understanding of the aspects of pawn law and pawn business in realizing legal protection for consumers. The method used in community service uses a directed discussion method, starting with the provision of material followed by discussion and question and answer directly through the Legal Core Program. This legal counseling is carried out with the target audience of the people of Bandung City and its surroundings. The results of this community service show that understanding of the legal aspects of pawning and pawning business increases public awareness and knowledge about the legal aspects of pawning and pawning business in accordance with the provisions of laws and regulations. Legal protection for society and consumers both preventively and repressively